2004
DOI: 10.1081/erc-200027356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Sibutramine or Orlistat Versus Their Combination in Obese Women

Abstract: These three regimens had different results on weight loss in obese women. Combination drug therapy and sibutramine therapy were both more effective than orlistat therapy alone. However, no significant difference was noted between combination drug therapy and sibutramine treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…Identical effectiveness of both continuous and intermittent drug administration was demonstrated for several anti-obesity drugs (47). Combination treatment with sibutramine and orlistat does not influence weight loss (48). However, in the future, combination therapy with anti-obesity drugs should be expected.…”
Section: Psychological Factors and Behavioralmentioning
confidence: 99%
“…Identical effectiveness of both continuous and intermittent drug administration was demonstrated for several anti-obesity drugs (47). Combination treatment with sibutramine and orlistat does not influence weight loss (48). However, in the future, combination therapy with anti-obesity drugs should be expected.…”
Section: Psychological Factors and Behavioralmentioning
confidence: 99%
“…Sibutramine (10-20 mg/day for 12 weeks to 12 months) reduced body weight and BMI more than orlistat (360 mg/day) in three studies in obese patients (total n = 325). [133][134][135] However, in two other studies (total n = 259), sibutramine (10 mg/day given for 12-24 weeks) and orlistat (360 mg/day) induced similar reductions in body weight, BMI, and waist circumference. 136,137 In another study in 115 hypertensive obese patients, sibutramine (10 mg/day given for 12 months) and orlistat (360 mg/day) reduced body weight, BMI, waist circumference and WHR to a similar extent.…”
Section: Comparative Studies With Other Antiobesity Agentsmentioning
confidence: 99%
“…138,140 Combining sibutramine and orlistat (10 mg and 360 mg/day, respectively, for 3-6 months) did not provide additional benefits over sibutramine monotherapy in obese patients. 133,134 Interestingly, a small study in 34 women who had received sibutramine for one year showed that adding orlistat to sibutramine for 16 weeks did not induce further weight loss. 141 In another study in 198 obese patients, combining sibutramine with an experimental selective antagonist of the receptor 5 of the orexigenic neuropeptide Y did not result …”
Section: Comparative Studies With Other Antiobesity Agentsmentioning
confidence: 99%
“…A third study, also of 6 months' duration, randomized 89 obese women to orlistat, sibutramine, or the combination and showed weight losses of 5.5, 10.1, and 10.8 kg, respectively. The combination was superior to orlistat but not to sibutramine alone (Sari et al, 2004). A fourth study randomized 86 obese subjects to 10 mg/day of sibutramine, 360 mg/day of orlistat, the combination, or diet alone.…”
Section: Studies In Childrenmentioning
confidence: 99%